2022
DOI: 10.1039/d1lc01161h
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and application of a liver-on-a-chip device in combination with modelling and simulation for quantitative drug metabolism studies

Abstract: Microphysiological systems (MPS) are complex and more physiologically realistic cellular in vitro tools that aim to provide more relevant human in vitro data for quantitative prediction of clinical pharmacokinetics while...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 58 publications
2
50
0
Order By: Relevance
“…9 In both studies, the authors reported modeling of experimental data to estimate PK parameters, but did not use drugs for which intestinal compartment metabolism played an important role. 3,4 The work presented in this paper builds upon these achievements, other MPS work involving prodrugs 10,11 and also our recently reported liver-on-a-chip MPS validation work, 6 with particular emphasis on the mechanistic study of prodrug absorption and activation in the gut, a highly relevant ADME application for gut–liver MPS.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…9 In both studies, the authors reported modeling of experimental data to estimate PK parameters, but did not use drugs for which intestinal compartment metabolism played an important role. 3,4 The work presented in this paper builds upon these achievements, other MPS work involving prodrugs 10,11 and also our recently reported liver-on-a-chip MPS validation work, 6 with particular emphasis on the mechanistic study of prodrug absorption and activation in the gut, a highly relevant ADME application for gut–liver MPS.…”
Section: Introductionmentioning
confidence: 89%
“…Cryopreserved hepatocytes were seeded in the scaffold in the liver compartment as reported previously. 6 A detailed description of the system preparation and incubation methods is provided in the ESI. †…”
Section: Biological Systems In the Gut And Liver Mps Compartmentsmentioning
confidence: 99%
See 3 more Smart Citations